Coastal Eukaryotic Plankton Diversity of the Southern Adriatic as Revealed by Metabarcoding - Ana Baricevic; Tjasa Kogovsek; Mirta Smodlaka Tankovic; Lana Grizancic; Mia Knjaz; Ivan Vlasicek; Ivan Podolsak; Natasa Kuzat; Martin Pfannkuchen; Daniela Maric Pfannkuchen (Diversity, 2024)
Plankton studies serve as a basis for marine ecosystem research, but knowledge of marine plankton is still incomplete due to its extreme taxonomic and functional complexity. The application of metabarcoding is very valuable for the characterisation of the plankton community. The plankton community of the Southern Adriatic is subject to strong environmental fluctuations and changes, which underlines the need for frequent, reliable and comprehensive characterisation of the plankton. The aim of this study was to determine the taxonomic composition and seasonal distribution of eukaryotic plankton in the Southern Adriatic. Plankton samples were collected monthly for one year at the coastal station of the Southern Adriatic and metabarcoding was used for taxonomic identification. The results showed a high taxonomic diversity and dynamic seasonal distribution patterns for both the protist and metazoan plankton communities. Metabarcoding revealed both the core, year-round plankton community and previously unrecorded plankton organisms in the Southern Adriatic. The results provide for the first time a comprehensive overview of the plankton community in this area by metabarcoding. The identified seasonal patterns of plankton genera and species in the Southern Adriatic will contribute to the understanding of plankton interactions and future changes in community diversity characterisation.